2022
DOI: 10.1021/acschemneuro.2c00221
|View full text |Cite
|
Sign up to set email alerts
|

Monosialotetrahexosylganglioside Promotes Early Aβ42 Oligomer Formation and Maintenance

Abstract: The aggregation of the amyloid beta (Aβ) peptide is associated with Alzheimer's disease (AD) pathogenesis. Cell membrane composition, especially monosialotetrahexosylganglioside (GM1), is known to promote the formation of Aβ fibrils, yet little is known about the roles of GM1 in the early steps of Aβ oligomer formation. Here, by using GM1-contained liposomes as a mimic of the neuronal cell membrane, we demonstrate that GM1 is a critical trigger of Aβ oligomerization and aggregation. We find that GM1 not only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(69 citation statements)
references
References 86 publications
5
64
0
Order By: Relevance
“…The protofibrils finally grow into mature fibrils during the mature phase. According to physiopathological and biochemical studies, all Aβ products, including monomers, oligomers, protofibrils, and fibrils, formed during the aggregation process are toxic, while the low-order Aβ oligomers generated in the lag phase are the most neurotoxic among all products. …”
Section: Introductionmentioning
confidence: 99%
“…The protofibrils finally grow into mature fibrils during the mature phase. According to physiopathological and biochemical studies, all Aβ products, including monomers, oligomers, protofibrils, and fibrils, formed during the aggregation process are toxic, while the low-order Aβ oligomers generated in the lag phase are the most neurotoxic among all products. …”
Section: Introductionmentioning
confidence: 99%
“…The results show that Aβ42 peptides attached to the membrane and interacted preferentially with ganglioside GM1 (Figure C). Experimentally, Zhang et al later showed that GM1 promotes early Aβ42 oligomer formation in liposomes and helps to maintain the amyloid structure . The authors then mutated the Arg residue responsible for GM1 binding in MD simulations and found much more disassociation of Aβ42 from the membrane.…”
Section: Membrane-active Peptides/peripheral Proteinsmentioning
confidence: 99%
“…Early studies suggested that Aβ fibrils are the toxic agents that cause neuronal cell death and other hallmarks of AD. Further studies have shown that Aβ oligomers rather than Aβ fibrils are toxic to neuronal cells (G. Chen et al, 2017; D. Y. Zhang et al, 2022). Bernstein et al determined that the aggregation prone form of Aβ, Aβ42, has a different oligomer‐size distribution than the more commonly found form, Aβ40 (Bernstein et al, 2009).…”
Section: Protein Aggregation In Diseasementioning
confidence: 99%
“…They further computationally substituted R5 to glycine, and they found that the average distance between G5 and GM1 increased to >10 Å and was within a binding distance (<2 Å) for as little as 2% of the time, indicating that the R5G mutation disrupted the tight binding interaction between the fifth residue and GM1. Thus, the fifth residue in Aβ42 plays a critical role in the direct binding between AC and GM1 (D. Y. Zhang et al, 2022). The recently‐solved cryo‐EM structures of Aβ have provided valuable insights into the molecular architecture of amyloid fibrils and their role in the pathogenesis of Alzheimer disease (Fitzpatrick et al, 2017; Gremer et al, 2017; Q. Li et al, 2021; R. Zhang et al, 2009).…”
Section: Modeling Protein Aggregationmentioning
confidence: 99%
See 1 more Smart Citation